Conflict and Development : Lessons from South Asia - Ghani, Ejaz; Iyer, Lakshmi (World Bank, Washington, DC, 2012)
South Asia is the second most violent place on earth after Iraq. Conflicts in Afghanistan and Pakistan have attracted global attention. Parts of India, Sri Lanka, and Nepal have experienced long-running conflict. Conflicts result in death, misery, social trauma, destruction of infrastructure, and have huge spillover effects. What is conflict? Where is it concentrated? Is conflict a problem for development, or a failure of development? And what should policy makers do?